Chronic Stress Suppresses the Expression of Cutaneous Hypothalamic–Pituitary–Adrenocortical Axis Elements and Melanogenesis - Pang, Silin; Wu, Huali; Wang, Qian; Cai, Minxuan; Shi, Weimin; Shang, Jing (PLOS ONE, 2014)
Chronic stress can affect skin function, and some skin diseases might be triggered or aggravated by stress. Stress can activate the central hypothalamic–pituitary–adrenocortical (HPA) axis, which causes glucocorticoid levels to increase. The skin has HPA axis elements that react to environmental stressors to regulate skin functions, such as melanogenesis. This study explores the mechanism whereby chronic stress affects skin pigmentation, focusing on the HPA axis, and investigates the role of glucocorticoids in this pathway. We exposed C57BL/6 male mice to two types of chronic stress, chronic restraint stress (CRS) and chronic unpredictable mild stress (CUMS). Mice subjected to either stress condition showed reduced melanogenesis. Interestingly, CRS and CUMS triggered reductions in the mRNA expression levels of key factors involved in the HPA axis in the skin. In mice administered corticosterone, decreased melanin synthesis and reduced expression of HPA axis elements were observed. The reduced expression of HPA axis elements and melanogenesis in the skin of stressed mice were reversed by RU486 (a glucocorticoid receptor antagonist) treatment. Glucocorticoids had no significant inhibitory effect on melanogenesis in vitro. These results suggest that, high levels of serum corticosterone induced by chronic stress can reduce the expression of elements of the skin HPA axis by glucocorticoid-dependent negative feedback. These activities can eventually result in decreased skin pigmentation. Our findings raise the possibility that chronic stress could be a risk factor for depigmentation by disrupting the cutaneous HPA axis and should prompt dermatologists to exercise more caution when using glucocorticoids for treatment.